Case report: Portal vein ligation: lessons from patients with PRETEXT III hepatoblastoma in restoring future liver remnant before major hepatectomy and literature review - Gang, Suiin; Ha, Suhyeon; Kwon, Hyunhee; Park, Jueun; Namgoong, Jung-Man (Frontiers in Surgery, 2023)
Background: We describe three cases involving three patients with PRETEXT III hepatoblastoma invading the hepatic hilum. After portal vein embolization, the patients underwent uncomplicated trisectionectomy. Methods: Medical records between March 2016 and March 2021 were reviewed, and three patients were selected. A literature review of techniques for increasing future liver remnant in children diagnosed with hepatoblastoma was also conducted. Results: All tumors involved the right lobe and hepatic hilum (PRETEXT III). After neoadjuvant chemotherapy, the tumor size decreased, but hilar involvement was unimproved. Right portal vein ligation (RPVL) was performed to increase the left lobe volume. Post-ligation, the remnant liver increased. Liver function was restored to normal levels within 5 days after the hepatectomy. All patients underwent two cycles of adjuvant chemotherapy without tumor recurrence. Conclusions: RPVL can be safely performed before extended hepatic resection in children with a giant hepatoblastoma invading the hepatic hilum. The tumor was completely resected by securing a sufficient margin and increasing the residual liver volume with portal vein embolization. The patients recovered and underwent adjuvant chemotherapy without the deterioration of liver function.